Diffraction by a rectangular groove with resistive waits - Sahinkaya, DSA; Büyükaksoy, A (Elsevier Gmbh, 2005)
The plane wave diffraction from a rectangular groove having resistive vertical walls with material loading is analyzed for E polarization by using the Fourier transform technique. The problem is formulated into a modified Wiener-Hopf equation applying boundary conditions. The modified Wiener-Hopf equation is solved via the factorization and decomposition procedure. The scattered field is evaluated by taking the inverse Fourier transform and applying the saddle point method. Numerical results on the backscatter radar cross-section (RCS) patterns are presented for various physical parameters. (c) 2004 Elsevier GmbH. All rights reserved.
Keywords: diffraction; rectangular groove; Wiener-Hopf technique